Calibrating the instrumental drift in MAROON-X using an ensemble analysis - Basant, Ritvik; Das, Tanya; Bean, Jacob L.; Luque, Rafael; Seifahrt, Andreas; Brady, Madison; Brown, Nina; Stürmer, Julian; Kasper, David; Stefánsson, Guđmundur (The astronomical journal, 2025)
MAROON-X is a state-of-the-art extreme-precision radial velocity spectrograph deployed on the 8.1 m Gemini-N telescope on Maunakea, Hawai’i. Using a stabilized Fabry-Pérot etalon for wavelength and drift calibration, MAROON-X has achieved a short-term precision of ∼30 cm s−1. However, due to a long-term drift in the etalon (2.2 cm s−1 per day) and various interruptions of the instrument baseline over the first few years of operation, MAROON-X experiences radial velocity (RV) offsets between observing runs several times larger than the short-term precision during any individual run, which hinders the detection of longer-period signals. In this study, we analyze RV measurements of 11 targets that either exhibit small RV scatter or have signals that can be precisely constrained using Keplerian or Gaussian process models. Leveraging this ensemble, we calibrate MAROON-X’s run offsets for data collected between 2020 September and early 2024 January to a precision of ∼0.5 m s−1. When applying these calibrated offsets to HD 3651, a quiet star, we obtain residual velocities with an rms of <70 cm s−1 in both the red and blue channels of MAROON-X over a baseline of 29 months. We also demonstrate the sensitivity of MAROON-X data calibrated with these offsets through a series of injection-recovery tests. Based on our findings, MAROON-X is capable of detecting sub m s−1 signals out to periods of more than 1000 days.
Gesehen am 02.10.2025